Teacher and student perceptions of the goals of global education - Appleyard, Natalie (University of Ottawa (Canada), 2009)
This qualitative case study analyses how the goals of global education are perceived by teachers and students of one high school currently involved in a global education program. My central question is: "How do students and teachers currently involved in a global education program in one rural Ontario high school perceive the goals of global education?" Participants included a principal, five teachers, and five students involved in a pilot global education program for grade nine students at a small, homogeneous, rural high school in Ontario. This study presents their specific context and perspectives in order to contribute to a deeper understanding of the nature, transference, and effects of the goals of global education. Data was collected through individual interviews, a focus group, and one classroom observation. Findings suggest staff and student participants share many similar perceptions of the goals of global education such as increasing students' global and cultural awareness; broadening students' perspectives; engaging students in their own learning; and preparing students for the future. Divergent perceptions among students such as what was meant by the term "global education" and a greater emphasis on helping others through a charity model suggest implications for improving consistency between the greater goals of global education and its implementation. Participants' responses further reveal perceptions of barriers and sources of support for the goals of global education specific to their rural, homogenous context, as well as those common to global educators across North America and the U.K. represented in the extant literature.
Keywords: Education, Administration.